Digital leadership in enhancing research innovation culture in higher education: Avenue for further research - Anindhyta, Chyta; Karnati, Neti; Suryadi, Suryadi (UIN Raden Mas Said Surakarta, 2023)
The world has recently encountered an unexpected condition - Covid-19, which has sparked a growing interest in educational leadership research, particularly in higher education. This interest is driven by the need to create an environment that fosters collaboration, openness to improvement, and adaptability in the face of unforeseen challenges. Among the topics gaining prominence in higher education is Digital Leadership, a blend of transformational leadership and digital technology. This study aims to bridge the gap between theory and practice in order to enhance the Research Innovation Culture in Higher Education within the context of educational leadership in the 21st century. A systematic review analysis was conducted to provide an overview of existing literature on digital leadership quality, research innovation culture in universities, and the future trajectory of educational leadership in the 21st century. The analysis identified key problems requiring further investigation and revealed patterns of theories and methods employed by previous researchers and participants. The findings indicated a clear correlation between the application of digital leadership and the enhancement of research and innovation culture in universities. Consequently, the implications of this research call for the establishment of a research and innovation culture that optimizes the Tri Dharma of Higher Education. By improving educational leadership and promoting digital leadership, universities can build a foundation for future growth and development. Embracing a research and innovation culture will not only help address unforeseen challenges but also lead to valuable outcomes that benefit higher education institutions and society as a whole.